Interleukin-8 genetic diversity, haplotype structure and production differ in two ethnically distinct South African populations. (July 2021) - Paximadis, Maria; Picton, Anabela C.P.; Sengupta, Dhriti; Ramsay, Michele; Puren, Adrian; Tiemessen, Caroline T.
Highlights: The IL-8 −251A > T SNP is differentially linked to downstream variants in black and white South African individuals. Peripheral blood mononuclear cells from white individuals produce more IL-8 than black individuals upon stimulation. Newly identified haplotypes and variants that associate with higher IL-8 production in black individuals. South African black individuals may be high IL-8 producers compared to other sub-Saharan African populations. Abstract: A single nucleotide polymorphism (SNP), 251 bases upstream from the IL-8 transcription start (−251A>T, rs4073), has been extensively investigated in cancers and inflammatory and infectious diseases in predominantly European and Asian populations. We sequenced the IL-8 gene of 109 black and 32 white South African (SA) individuals and conducted detailed characterization of gene variation and haplotype structure. IL-8 production in phytohaemagglutinin (PHA)-stimulated peripheral blood mononuclear cells (PBMCs) of a subset (black: N = 22; white: N = 32) of these individuals was measured using ELISA. Select variants were genotyped for additional black individuals (N = 141), and data from the 1000 Genomes Project were used for haplotype analysis and comparative purposes. In white individuals, the −251A>T SNP formed part of a prevalent six-variant haplotype [haplotype frequency (HF): 61%], Hap-1C, involving the following variants: −251A>T; +394T>G (rs2227307); +780C>T (rs2227306); +1240->A (rs2227541); +1635C>T (rs2227543) and +2770A>T (rs2227543). Hap-1C (−251T +394T +780C +1240+ A +1635C +2770A ) was composed of two three-variant sub-haplotypes [Hap-1Ca: −251T +394T +1240+ A ; Hap-1Cb: +780C +1635C +2770A ) sharing similarities with haplotypes identified in the black population. Hap-1C was found to be present in European, East and South Asian populations. Four haplotypes were identified in the black population with the two prevalent haplotypes each comprised of two variants: Hap-1B [−251A>T and +1240->A; −251T +1240+ A ; HF: 14%] and Hap-2B [−743T>C (rs2227532) and +2452A>C (rs2227545); −743C +2452C ; HF: 13%]. Populations did not differ in unstimulated PBMC IL-8 production. Upon PHA stimulation, PBMCs from white individuals produced more IL-8 (P = 0.04), suggesting the −251T allele is responsible for higher production, however further analysis revealed that Hap-1C (and constituent sub-haplotypes), did not associate with IL-8 production. Populations did however differ in monocyte number with the white population having significantly more monocytes compared to the black population (P = 0.025), and furthermore monocyte number strongly correlated with IL-8 production in both population groups (black: p = 0.0002, r = 0.71; white: P = 0.0005, r = 0.59). Hap-1B, Hap-2B, and a SNP located one base pair upstream of the IL-8 ATG start codon, +100C>T SNP (rs2227538), all associated with higher IL-8 production in the black population - individuals harbouring at least one of these haplotypes/variant associated with higher IL-8 production (P = 0.003) compared to individuals without. The black population was enriched for individuals harbouring Hap-1B and/or Hap-2B compared to the 1000 Genomes project sub-Saharan African population (P = 0.006), suggesting that SA black individuals may be high IL-8 producers. Given the paucity of IL-8-related studies that have been conducted in populations from sub-Saharan Africa, this study has significantly increased our understanding of this important chemokine in the South African population.